Comparing the Effectiveness of Four Different Design Media in Communicating Desired Performance Outcomes With Clinical End Users. (April 2019) - Wingler, Deborah; Machry, Herninia; Bayramzadeh, Sara; Joseph, Anjali; Allison, David
Objective: The purpose of this study was to compare the effectiveness of four different design communication media in helping clinical end users understand spatial and functional information and in supporting their ability to provide design feedback. Background: It is critical to involve clinical end users early in the design process to test design solutions and ensure the design of a new healthcare facility supports their ability to deliver high-quality care. Traditional architectural design communication media such as floor plans and perspectives can be challenging for clinical design team members to understand. Physical and virtual mock-ups are becoming more popular as design communication media. However, nominal evidence exists comparing the effectiveness of different design media in supporting clinical end-user engagement and contribution during the design process. Method: An exploratory, qualitative study was conducted with clinical end users to evaluate the effectiveness of four different media commonly used in design communication. Results: Traditional architectural representations convey limited useful information to clinical end users, impacting the amount and type of feedback they can provide. More immersive media, such as physical and virtual mock-ups, support an increasingly holistic understanding of proposed design solutions, inciting more design solutions that range from the inclusion and exclusion of design features to location, position, and functionality of those features. Conclusions: When used in combination, each media can contribute to eliciting clinical end-user feedback at varying scales. The overall preference and higher effectiveness in eliciting design feedback from clinical end users highlights the importance of physical mock-up in communicating healthcare design solutions.